2016
DOI: 10.1002/pmic.201500501
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of mitochondrial pyruvate dehydrogenase subunit dihydrolipoamide dehydrogenase protein–protein interactions by the MDM2 ligand nutlin‐3

Abstract: Drugs targeting MDM2's hydrophobic pocket activate p53. However, these agents act allosterically and have agonist effects on MDM2's protein interaction landscape. Dominant p53‐independent MDM2‐drug responsive‐binding proteins have not been stratified. We used as a variable the differential expression of MDM2 protein as a function of cell density to identify Nutlin‐3 responsive MDM2‐binding proteins that are perturbed independent of cell density using SWATH‐MS. Dihydrolipoamide dehydrogenase, the E3 subunit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…MDM2 is described to bind to over 100 proteins, yet little is known about how all these interactions relate to the cell biology of MDM2. Small molecules targeting MDM2 alter the binding of its associated proteins by either directly disrupting the MDM2 interface required for association ---and/or ---promote numerous allosteric changes in multiple MDM2 domains directly, thus altering motifs to that either gain or lose capacity to interact with proteins (Janssen et al, 2006;Way et al, 2016). Here, we noted that Nutlin-3A could enhance the interaction between MDM2 and NDUFS1 (Fig.…”
Section: Mdm2 Integrates Mitochondrial Ros Production Genomic Stressmentioning
confidence: 66%
See 2 more Smart Citations
“…MDM2 is described to bind to over 100 proteins, yet little is known about how all these interactions relate to the cell biology of MDM2. Small molecules targeting MDM2 alter the binding of its associated proteins by either directly disrupting the MDM2 interface required for association ---and/or ---promote numerous allosteric changes in multiple MDM2 domains directly, thus altering motifs to that either gain or lose capacity to interact with proteins (Janssen et al, 2006;Way et al, 2016). Here, we noted that Nutlin-3A could enhance the interaction between MDM2 and NDUFS1 (Fig.…”
Section: Mdm2 Integrates Mitochondrial Ros Production Genomic Stressmentioning
confidence: 66%
“…Therefore, we examined the impact of SOD1 co-expression on MDM2 WT -and MDM2 1-101 -induced mitochondrial ROS production, DNA damage, and subsequent apoptosis in H1299. As demonstrated before, MDM2 WT or MDM2 1-101 lead to increased mitochondrial ROS, H2AX accumulation, and apoptosis; and co-expression of SOD1 was effective in preventing the majority of these stress phenotypes Several studies have highlighted the importance of gaining a broader perspective of the MDM2 interactome, and its regulation by small molecules like Nutlin-3A (Janssen et al, 2006;Way et al, 2016). MDM2 is described to bind to over 100 proteins, yet little is known about how all these interactions relate to the cell biology of MDM2.…”
Section: Mdm2 Integrates Mitochondrial Ros Production Genomic Stressmentioning
confidence: 76%
See 1 more Smart Citation
“…The Nutlin-3 responsive proteins can be stratified with respect to p53-like "BOX-I" homology motifs that identify a relatively large set of p53-like MDM2 binding proteins whose equilibrium binding to MDM2 is disturbed by Nutlin-3 [26]. Mass spectrometry demonstrated that mitochondrial protein interactions are perturbed by Nutlin-3, which induces an increase of MDM2 binding to the dihydrolipoamide dehydrogenase (DLD) subunit of mitochondrial pyruvate dehydrogenase in the nucleus [27]. Thus, the balance between tumor suppressor induction and oncoprotein activation by MDM2-targeted drugs could tip the balance towards tumor regression or tumor survival, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that these proteins were acetylated and crotonylated according to their function in lipid metabolism. 9,10 We then summarized the dynamic changes of acetylation and crotonylation sites in Dld and Acat1 proteins.…”
mentioning
confidence: 99%